Spectroscopic Studies of Fluorescence Effects in Bioactive 4-(5-Heptyl-1,3,4-Thiadiazol-2-yl)Benzene-1,3-Diol and 4-(5-Methyl-1,3,4-Thiadiazol-2-yl)Benzene-1,3-Diol Molecules Induced by pH Changes in Aqueous Solutions - Matwijczuk, Arkadiusz (J Fluoresc, 2017)
This paper presents the results of stationary fluorescence spectroscopy and time-resolved spectroscopy analyses of two 1,3,4-thiadiazole analogues, i.e. 4-(5-methyl-1,3,4-thiadiazol-2-yl)benzene-1,3-diol (C1) and 4-(5-heptyl-1,3,4-thiadiazol-2-yl)benzene-1,3-diol (C7) in an aqueous medium containing different concentrations of hydrogen ions. An interesting dual florescence effect was observed when both compounds were dissolved in aqueous solutions at pH below 7 for C1 and 7.5 for C7. In turn, for C1 and C7 dissolved in water at pH higher than the physiological value (mentioned above), single fluorescence was only noted. Based on previous results of investigations of the selected 1,3,4-thiadiazole compounds, it was noted that the presented effects were associated with both conformational changes in the analysed molecules and charge transfer (CT) effects, which were influenced by the aggregation factor. However, in the case of C1 and C7, the dual fluorescence effects were visible in a higher energetic region (different than that observed in the 1,3,4-thiadiazoles studied previously). Measurements of the fluorescence lifetimes in a medium characterised by different concentrations of hydrogen ions revealed clear lengthening of the excited-state lifetime in a pH range at which dual fluorescence effects can be observed. An important finding of the investigations presented in this article is the fact that the spectroscopic effects observed not only are interesting from the cognitive point of view but also can help in development of an appropriate theoretical model of molecular interactions responsible for the dual fluorescence effects in the analysed 1,3,4-thiadiazoles. Furthermore, the study will clarify a broad range of biological and pharmaceutical applications of these compounds, which are more frequently used in clinical therapies. [Figure: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10895-017-2053-y) contains supplementary material, which is available to authorized users.